Cryptocurrency: Highlighting the Approach, Regulations, and Protection in Indonesia and European Union - Tauda, Gunawan A.; Omara, Andy; Arnone, Gioia (BESTUUR, 2023)
The speed of the adoption and use of cryptocurrency that utilizes blockchain technology as its central infrastructure is expanding globally, including in Indonesia. It has promising prospects as a future asset and payment instrument. However, the regulations in Indonesia are often delayed and inadequate for dealing with cryptocurrency's developments. This research is intended to analyze the approaches, regulations, and protection of the use of cryptocurrency. This study argues that the regulatory approach to using cryptocurrency is balanced, while Indonesia has a partial status in cryptocurrency legality. The government’s protection of cryptocurrency investors is adequate in using cryptocurrency as a commodity traded on futures exchanges with a license from Bappebti. A progressive policy for establishing the Digital Asset Law by the government is important due to the resultant clarity in the regulatory status of cryptocurrency will allow the ecosystem to grow and promote innovation, thus harnessing the benefits of cryptocurrency while mitigating related risks.